Physical, optical and thermoluminescence properties of lithium aluminum borate glass co-doped with Dy2O3 - Aljewaw, O.B.; Karim, M.K.A.; Effendy, N.; Kamari, H.M.; Zaid, M.H.M.; Noor, N. M.; Salim, A.A.; Isa, N.M.; Kadir, A.B.A.; Chew, Ming Tsuey *; Abokridiga, A.I. (Elsevier, 2023)
The present study aimed to evaluate the physical, optical, and thermoluminescence (TL) properties of Li2O–Al2O3–B2O3 as a function of adding Dy2O3 dopant concentrations varying from 0.0 to 0.8 mol%. The glasses were produced through the melt-quenching technique. The optimal concentration of Dy3+ ions for the 4F9/2 → 6H11/2 and 4F9/2 → 6H15/2 transition was found to be at 0.8 mol%. The glassy nature of the quenched samples was confirmed by the XRD pattern. All samples have been subjected to measurements of various physical properties, including density, molar volume, Polaron radius, inter-nuclear distance, ion concentration, and field strength. The most optimal sample exhibited exceptional linearity within the dose range of 0.5–5.0 Gy during gamma irradiation. The un-doped and Dy3+ doped glasses exhibited a linear correlation coefficient of 0.446 and 0.995, respectively, while their tissue-equivalent effective atomic numbers were 7.4 and 10.5. Over the course of a month, the glasses exhibited a fading rate of only 15%. After being exposed to 3.0 Gy of gamma rays, the samples for minimum detectable dose and reproducibility were examined. The kinetic parameters of the glasses under investigation, such as activation energies and kinetics orders, were determined using the peak shape method. According to the findings, the sample that contained 0.8 mol% of Dy2O3 exhibited exceptional thermoluminescence characteristics, indicating its potential as a dosimeter for measuring exposure to ionizing radiation.